Technological Transitions: Ai In Language Teaching And Learning. L2 Written Productions And Ai Generated Texts. - Johnson, Athena (The Journal of Studies in Language, Culture, and Society, 2025)
This exploratory study proposes an investigation into AI-generated productions compared to L2 student-written productions within the context of English Language Learning. Initiated within a broader pedagogical shift from handwritten to typed productions, and coinciding with the rise of AI tools such as ChatGPT, the study examines challenges related to AI in language teaching, underscoring the importance of understanding and framing the interaction with AI tools in light of the challenges. The study draws on data from 58 French university students enrolled in an intermediate-level English course. Participants were tasked with composing written syntheses in typed forms. The students' texts were then compared with AI-generated texts created in response to the same prompts. A mixed-methods approach, combining both quantitative and qualitative analysis, was used to examine linguistic, discursive, and structural features across the two corpora. Findings reveal notable differences in stylistic complexity. The study explores the connections between the teacher and reinforcement learning in AI and reveals notable issues related to AI bias and explainability. The article concludes with a reflection on pedagogical implications of integrating AI tools into language learning, exploring how AI tools may support the needs of English language learners in a technological landscape that demands a balanced approach between awareness and adaptation to changes in written production.